Lost in Translation: Why Sport-based and Grassroots Activism May Be the Path to Equity in NIL Opportunities for International College Athletes - Newell, Emily; Kaur Sethi, Simran (Journal of Intercollegiate Sport, 2025)
International students have been tracked in U.S. higher education since 1924 (Witt, 2008). Today, nearly one million international students are studying at U.S. higher education institutions (HEIs), including more than 25,000 international college athletes (ICAs) who compete at National Collegiate Athletic Association (NCAA) member institutions (NCAA, 2023b). On July 1, 2021, the NCAA officially suspended its amateurism principle, and states began passing legislation to allow for student-athletes to monetize their Name, Image, and Likeness (NIL), bringing some closure to a more than a century-long debate over student-athlete compensation (NCAA, 2021b). However, the more than 25,000 NCAA ICAs are often left behind, unable to capitalize on most NIL opportunities due to work restrictions placed on F-1 student visas imposed by the Department of Homeland Security (DHS), the visas nearly all ICAs are granted (Witt, 2008). Although HEI administrators, athletics departments, and industry professionals have advocated on behalf of international students previously (Jordan & Hartocollis, 2020), there has been little effort to push for changes to visa restrictions that would provide ICAs equitable access to NIL opportunities, and more broadly, expand workforce experiences for international students. Therefore, the authors note the need for self-activism, potentially through a combined grassroots and sport-based model (Cooper et al., 2019), to achieve equal access to workforce, and in turn NIL, opportunities.